How to boost and reach the full potential of Mugler-s perfumes brand loyalty? - an analysis of loyalty programs in Portugal - Salzmann, Sarah (2022)
Mugler is having difficulties launching a loyalty program in Portugal because of the small size of its market and the brand's distribution model that makes it heavily dependent on retailers. GDPR regulations further do not allow the brand to access customer data. This individual part therefore aims to study how to establish a direct relationship with the Mugler consumer in Portugal through a loyalty program, taking into account the retail landscape. The main findings are that Mugler should seize the opportunity of merging with Spain, then adapt the Mugler Circle locally, and finally create awareness through offline and online channels.